Pengaruh Penggunaan Media Scrabble Terhadap Peningkatan Penguasaan Kosakata Bahasa Arab Siswa Kelas V di Madrasah Ibtidaiyah Darul Falah Oelaba - Dwi Yamila Yulianingsih; Yusron Hidayat (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to determine the effect of using the Scrabble game media on improving Arabic vocabulary mastery among fifth-grade students at Madrasah Ibtidaiyah Darul Falah Oelaba. The method used in this study is a quantitative design with a one-group pretest-posttest approach, involving the measurement of students’ vocabulary mastery before and after being given treatment using the Scrabble game. The results showed a significant improvement in students’ Arabic vocabulary mastery after using the Scrabble media. Statistical testing using the Wilcoxon test produced an Asymp. Sig. value of 0.001, indicating a significant difference between the students' pretest and posttest scores. The implication of this study is that the use of game-based media such as Scrabble can increase students’ active engagement in Arabic language learning, thereby helping them to master vocabulary more effectively. Nevertheless, the study also faced several challenges, such as the time needed for students to adapt to the game rules and limitations in tools during online learning. Therefore, further research is recommended to explore the application of game-based media under various learning conditions and with more diverse methods.